ANALYSIS OF THE INFLUENCE OF FISCAL POLICY ON ECONOMIC GROWTH WITH INVESTMENT AS A MODERATING VARIABLE IN INDONESIA - Tohap Parulian; A. Mahendra; Witya Shalini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to know the influence of tax and government expenditure on economic growth with investment as a moderating variable in Indonesia. The population in this research is Indonesia, and 24 of them were selected to be the samples for this research through a purposive sampling technique. This research uses multiple regression analysis techniques. This study's data type is secondary data, consisting of tax and government expenditure for economic growth for 2000-2024. This research showed that tax and government expenditures partially significantly affect economic growth in Indonesia. At the same time, simultaneously (f-test), Tax and Government Expenditure significantly affect the variables of Economic Growth. The investments cannot moderate the relationship between Tax and Government Expenditure on Economic Growth.